Customer Satisfaction and Loyalty Analysis Based on User Experience in Lalamove: Analisis Kepuasan dan Loyalitas Pelanggan Berbasis Pengalaman Pengguna di Lalamove - Tarigan, Feby Yola Br; Sumiati, Sumiati (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: The rapid advancement of information technology has transformed societal interaction patterns, notably through digital services such as delivery applications. Specific Background: One such service, Lalamove, provides practical and efficient instant delivery; however, user complaints persist. Knowledge Gap: Despite widespread adoption, there is limited academic insight into how user experience directly influences customer satisfaction and loyalty within this context. Aim: This study investigates customer satisfaction and loyalty toward the Lalamove application, focusing on user experience dimensions. Results: Using the HEART Framework to assess five aspects of user experience and the Net Promoter Score (NPS) to evaluate loyalty, findings reveal an overall usability score of 0.71 (71%), surpassing the predefined target of 70%, although several items remained below target. Meanwhile, the NPS loyalty score stood at 17%, indicating moderate loyalty where users continue using the app but are less inclined to recommend it. Novelty: This study integrates HEART and NPS in a comprehensive framework to bridge user experience and customer loyalty in a delivery service context. Implications: The findings underscore the need for targeted service improvements using the 5W+1H approach, offering actionable insights for enhancing user satisfaction and fostering sustained loyalty. Highlight: Integrated Metrics: Combines HEART and NPS for a comprehensive evaluation. User Loyalty Insight: Identifies moderate loyalty despite usability success. Actionable Solutions: Uses 5W+1H to propose focused service improvements. Keywords: User Experience, Customer Loyalty, HEART Framework, Net Promoter Score, Lalamove Application